FAKTOR FAKTOR YANG MEMPENGARUHI KEJADIAN DISMENOREA PRIMER PADA REMAJA AKHIR - Raudatul Jannah; Oswati Hasanah; Rismadefi Woferst (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2022)
The incidence of dysmenorrhea based on WHO is very large, namely more than 50% of women of reproductive age experience dysmenorrhea and peaks in their early 20s, namely in the late teenage age range and causes the inability to carry out daily activities for 1 to 3 days each month. The factors that influence dysmenorrhea are age at menarche, length of menstruation, family history, nutritional status, and exercise. The purpose of this study was to determine the factors that influence the incidence of primary dysmenorrhea in late adolescence. This study uses descriptive correlation. This research was conducted at the Faculty of Nursing, Riau University with 229 samples taken using random sampling technique with inclusion criteria. The measuring instrument used is an online questionnaire that has been tested for validity and reliability. The analysis used is a univariate and bivariate analysis using the chi-square test. This univariate study found respondents who experienced primary dysmenorrhea as many as 88.6%, normal age of menarche of 90.4%, a normal menstrual period of 82.5%, had a family history of 54.6%, nutritional status risk of 53.3%, exercise 3-5 times per week with a duration of >30 minutes 94.3%, bivariate results showed there was a significant relationship between family history and primary dysmenorrhea (p=0.01) and there was no significant relationship between age at menarche (p=0.147), duration of menstruation (p=0,270), nutritional status (p=0,632), exercise (0,647) with primary dysmenorrhea. Based on the results of this study, the researchers concluded that the factors of age at menarche, duration of menstruation, nutritional status, and exercise did not have a relationship with the incidence of primary dysmenorrhea, while family history had a relationship with the incidence of primary dysmenorrhea as evidenced by statistical data with a p-value <0.05.Keywords: Affecting factors; dysmenorrhea; late adolescence